2018
DOI: 10.1021/acs.jpcc.8b00798
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hydrogen Sulfide Exposure on the Transport and Structural Properties of the Metal–Organic Framework ZIF-8

Abstract: The interaction between hydrogen sulfide and ZIF-8 was studied via structural characterizations and guest molecule diffusion measurements. It was found that hydrogen sulfide reacts with the ZIF-8 external particle surface to form a surface barrier that excludes the uptake of larger molecules (ethanol) and slows down the uptake of smaller molecules (carbon dioxide). Nonetheless, bulk transport properties were unaltered, as supported by pulsed field gradient nuclear magnetic resonance studies. Dispersion-correct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 45 publications
4
26
0
Order By: Relevance
“…The diffusion of fluids in the pores of MOFs can be evaluated by experimental and theoretical approaches. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Amongst these, the combination of pulsed field gradient (PFG) NMR and molecular dynamics (MD) simulations represents a powerful complimentary approach to enable the exploration of diffusion at time-and length scales differing by orders of magnitude. 14,27,28 MD simulations can track molecular mobility within a single pore of ideal structures, while the PFG NMR is capable of direct probing of molecular displacements ranging from hundreds of nanometers to microns, i.e.…”
Section: Toc Graphicsmentioning
confidence: 99%
“…The diffusion of fluids in the pores of MOFs can be evaluated by experimental and theoretical approaches. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Amongst these, the combination of pulsed field gradient (PFG) NMR and molecular dynamics (MD) simulations represents a powerful complimentary approach to enable the exploration of diffusion at time-and length scales differing by orders of magnitude. 14,27,28 MD simulations can track molecular mobility within a single pore of ideal structures, while the PFG NMR is capable of direct probing of molecular displacements ranging from hundreds of nanometers to microns, i.e.…”
Section: Toc Graphicsmentioning
confidence: 99%
“…To date, some previouss tudies have already shown that exposure of MOFs to acidic gases can induce important structural changes. [15,16] Interestingly,t he activation energy associated with these gas-framework interactions, andt he associated side-effects, highly depends on the crystallographic orientation. For instance, Pang et al demonstrated that the (110) facets of ZIF-8 crystals are more reactive than the (100) facets under humid SO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…[15] Furthermore, whilet his structurald amage was mainly restricted to the external surface of ZIF-8 crystals, the bulk of these crystals remained mainly unchanged.R emarkably,D utta et al reported that the bulk properties of ZIF-8 were preserved after exposing it to H 2 S, showings imilar intraparticled iffusivities before and after acidt reatment. [16] Anisotropic acid etching of MOFs using HCl has also been used in the literature to obtain unprecedented morphologies due to the different reactivity among crystallographic directions. [17] These preliminarys tudies clearly anticipate that the composition of the effluent gas and, more specifically,t he presence of acidic contaminants can have ac rucial role in the performance and lifetimeo fM OFs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations